PROSPECTS FOR THE DEVELOPMENT OF TOURISM IN UZBEKISTAN - Norbekov, Khursandmurod; Karshibayev, Ziyadbek (Science technology&Digital finance, 2023)
The tourism (tourism) sector is one of the most dynamically developing sectors of the world economy. Its extensive progress is becoming a major source of income for many countries. The tourism sector has become one of the most important economic sectors of today. Therefore, many countries of the world are implementing all measures to further develop this area, create the appropriate infrastructure at the level of world standards in this regard and increase the flow of tourists.